(untitled) (Altre Modernità, 2021)
The Palio of Ronciglione has a centuries-old tradition, but what makes it truly unique is the absence of any jockey. When the canape falls, each horse chooses whether to compete with the others, to tag along or simply not to run, depending on different temperaments. In the context of the Palio, the horse represents a co-producer of cultural processes, which also transmits its experience to the younger specimens; this latter aspect is particularly evident in the trajectories chosen during the race, based on an indisputable non-human subjectivity. A first ‘internal’ form of inscription to the species should be noted: racehorses are the result of centuries-old domestication combined with a controlled genetic selection (breeding), which has gradually entangled Equus ferus caballus in human society. A second ‘external’ aspect concerns the racetrack, an environment of inter-species coexistence: created by the human community, it is crossed and experienced by horses, which engrave the urban tissue with their trajectories. The animal’s agency, therefore, emerges through the creative adaptation to the path, an inscription of non-human geometries in this space. The intentionality of the horse is what establishes the performance of the Palio: it may seem paradoxical, but the conservation of this cultural heritage is possible as long as the horse can choose not to run.